2011
DOI: 10.4103/0972-6748.102528
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-etiology delirium and catatonia in an alcoholic with tubercular meningoencephalitis

Abstract: Delirium is a clinical entity with a variety of possible etiological conditions. Clinicians must be vigilant for the possibility of additional etiological factors. Secondly, catatonic patients should be carefully looked for general medical conditions. This case report depicts a chronic alcoholic who presented with withdrawal delirium, later on developed catatonia and then was diagnosed to have tubercular meningoencephalitis, a rare clinical sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
3
1
1
Order By: Relevance
“…The frequency of delirium in the context of the patients’ clinical presentations of ME in our study is in contrast to the few case reports and case series 26 28 reporting on delirium with ME and the lack of cohort studies in this context. The latter seems likely to mirror the lack of awareness regarding the coexistence of delirium and the clinical presentation of ME.…”
Section: Discussioncontrasting
confidence: 87%
“…The frequency of delirium in the context of the patients’ clinical presentations of ME in our study is in contrast to the few case reports and case series 26 28 reporting on delirium with ME and the lack of cohort studies in this context. The latter seems likely to mirror the lack of awareness regarding the coexistence of delirium and the clinical presentation of ME.…”
Section: Discussioncontrasting
confidence: 87%
“…Los signos que pueden asociarse con el delírium hipoactivo son inmovilidad, retraimiento, adopción de posturas por largo tiempo, mutismo y negativismo. Con el delírium hiperactivo se asocian impulsividad, manierismos, excitación motora y combatividad 20 .…”
Section: Discussionunclassified
“…The authors suggested that catatonia may be a subtype of delirium . Further data from the literature in the form of case reports also suggest that delirium and catatonia may occur in the same patients concurrently or one may follow the other …”
mentioning
confidence: 99%
“…15 Further data from the literature in the form of case reports also suggest that delirium and catatonia may occur in the same patients concurrently or one may follow the other. [16][17][18][19][20] Major changes have been suggested for catatonia in DSM-5 to reduce under-recognition of this condition. According to the DSM-5 criteria, three out of the 12 criteria are required for the diagnosis of catatonia.…”
mentioning
confidence: 99%